PENINGKATAN EFISIENSI PRODUKSI AYAM PETELUR MELALUI PENINGKATAN KENYAMANAN KANDANG DI DESA BOLANGAN - I M. Nuriyasa. Eny Puspani; I G. N. Sum atra; P. P. Wibawa; I M. Mudita (Buletin Udayana Mengabdi, 2010)
The short course of improving broiler performances with more comfortable cage was conducted on September 25th. 2009 in Bolangan village, Tabanan regency. There were 15 local farmers and 18 SMK No1. Katiku Tanah, Sumbawa students as participants of this activity. The teams presented about (1) animal comfort zone, (2) cage modifications, (3) heat transfer between animal and environment and (4) energy protein ration. Based on the limited discussion, it could be seen that participants were very enthusiastic in joining this activity. They used this occasion for making discussion with the concerned team from Udayana University.